Desempenho de fontes lineares e chaveadas no contexto da qualidade da energia elétrica - Santos, Ana Cláudia Daroz dos (2001)
Nowadays, researches and developments in relation to Electrical Power Quality rise as major concerns for both international and national communities. Amongst the various areas of interest emerge that associated to the operation of electrical components and devices supplied by non-ideal systems. In this way, it is necessary to carry on studies in order to achieve a good knowledge of the relationship between residential, commercial and industrial loads and the quality of the supply. Thus, this dissertation goes into the direction of studying the behaviour of linear and switched sources under power quality disturbances conditions. By using typical devices, which contain such types of supply units, i.e. a radio/CD player and a microcomputer, studies are performed by means of computational and experimental strategies. The fírst equipment illustrates the linear source performance and the second the switched source. The results to be given show, amongst others, the sources dependence on the quality of the supply and provide means to know the degree of equipment sensitivity or immunity to the problems related to Power System Quality.